Digital Creativity in Early Childhood Education: How Teachers Transform Apps, Games, and Animation into Play-Based Learning - Sri Nurhayati; Ema Aprianti; Anita Rakhman; Prita Kartika (Jurnal Ilmiah Profesi Pendidikan, 2026)
Digital creativity in early childhood education requires more than the introduction of applications, games, and animation into classroom activities. This study examined how teachers transform digital tools into play-based learning that supports children’s exploration, imagination, and creative expression. Using a descriptive qualitative design supported by simple descriptive statistics, the study analyzed data from 25 early childhood education institutions in West Java and nearby districts. Data were collected through semi-structured interviews, questionnaire responses, and classroom documentation, then analyzed thematically to identify patterns of digital play implementation, teacher mediation, child engagement, institutional support, and curriculum integration. The findings show that digital applications were used by all participating institutions, while most teachers had designed application-based learning, connected digital play to daily learning themes, and used digital media for art, sound, storytelling, and animation. Children were consistently reported as enthusiastic and curious, suggesting that digital play can become a powerful motivational entry point for creative learning. However, the study also identified a significant implementation gap: only a small proportion of institutions had integrated digital play into the curriculum. Barriers included uneven teacher digital competence, limited devices, insufficient learning time, unstable internet access, informal assessment, and weak documentation practices. The study concludes that digital creativity in early childhood education is most meaningful when digital tools are guided by teachers, connected to children’s real-life experiences, integrated with non-digital play, and supported by institutional policy. The findings contribute a contextual understanding of the digital play paradox: high adoption and enthusiasm, but weak curricular embedding.